Case Report: Perspective of a Caregiver on Functional Outcomes Following Bilateral Lateral Pectoral Nerve Cryoneurotomy to Treat Spasticity in a Pediatric Patient With Cerebral Palsy - Jack Scobie; Paul Winston; Paul Winston (Frontiers Media S.A., 2021)
Spasticity is common and difficult to manage complication of cerebral palsy that significantly affects the function and quality of life of patients. This case study reports a 15-year-old male with quadriplegic cerebral palsy, Gross Motor Function Classification System 5 (GMFCS 5), who presented with significant bilateral adducted and internally rotated shoulders as a component of generalized spasticity. Spasticity in the lower limb of the patient had been treated with botulinum toxin A (BoNT-A) injections; however, the shoulder region was spared due to concerns of toxin spread and aspiration risk. Following diagnostic nerve blocks, the patient underwent bilateral cryoneurotomies of the right and left lateral pectoral nerves (LPNs) lasting 3.5 min for each lesion. One month after the cryoneurotomies, the range of motion (ROM) had improved from 86° to 133° on the right and 90° to 139° on the left. Improvements in ROM were retained at 9 months post-procedure. At 8.5 months following the cryoneurotomies, the caregiver reported improvements in upper body dressing, upper body washing, transferring, and the ability of the patient to remain sitting in his wheelchair for extended periods. Cryoneurotomy may be an effective procedure for improving shoulder ROM and specific functional outcomes for caregivers of patients with spasticity arising from cerebral palsy.